Pengembangan Media Ular Tangga tentang Lahirnya Pancasila untuk IPS Kelas V SD - Ade Ineu Raina Oktapiani; Sumardi Sumardi; Rosarina Giyartini (Universitas Pendidikan Indonesia (UPI), 2020)
Abstract This research is motivated because there is no media in social studies subjects regarding the history of the birth of Pancasila for grade V elementary school. Media that makes students interested and willing to take part in social studies learning with fun because social studies learning is often seen as a boring and boring subject. One of the studies in social studies is the history of the birth of Pancasila. This research aims to produce a snake ladder media design about the birth of Pancasila for fifth grade elementary school students, to know the feasibility of snake ladder media about the birth of Pancasila for fifth grade elementary school students and to produce a snake ladder media about the birth of Pancasila for fifth grade elementary school students. The method used in this study is the Design Based Research (DBR) model of Reeves, because the researcher developed a media, namely snakes and ladders media about the history of the birth of Pancasila. To obtain data, researchers used several data collection techniques, namely interviews, expert judgment (expert judgment), observation and questionnaire. Based on trials that have been done, the results of the study showed that the snake ladder media received a positive response from students, in the first phase of the student response showed a percentage of 93%, while in the second stage of the trial the student response showed a percentage of 98.75%. Based on the results of the validation by the material, media and pedagogical experts as well as the results of the trials conducted by the developed learning media, it was declared to be suitable for use. Thus the development of snakes and ladders media about the birth of Pancasila in social studies learning for fifth grade elementary school students, is appropriate for students to use in the learning process. AbstrakPenelitian ini dilatarbelakangi karena belum adanya media dalam mata pelajaran IPS mengenai sejarah Lahirnya Pancasila untuk kelas V Sekolah Dasar. Media yang membuat siswa tertarik serta mau mengikuti pembelajaran IPS dengan menyenangkan karena pembelajaran IPS seringkali dipandang sebagai mata pelajaran yang menjenuhkan dan membosankan. Salah satu kajian dalam mata pelajaran IPS yaitu tentang sejarah lahirnya Pancasila. Penelitan ini bertujuan untuk menghasilkan rancangan media ular tangga tentang lahirnya Pancasila untuk siswa kelas V Sekolah Dasar, mengetahui kelayakan media ular tangga tentang lahirnya Pancasila untuk siswa kelas V Sekolah Dasar dan menghasilkan media ular tangga tentang lahirnya Pancasila untuk siswa kelas V Sekolah Dasar. Metode yang digunakan dalam penelitian ini yaitu Design Based Research (DBR) model Reeves, karena peneliti mengembangkan sebuah media yaitu media ular tangga tentang sejarah lahirnya Pancasila. Untuk memperoleh data, peneliti menggunakan beberapa teknik pengumpulan data yaitu wawancara, expert judgement (penilaian para ahli), observasi dan angket. Berdasarkan uji coba yang telah dilakukan, hasil penelitian menunjukan bahwa media ular tangga mendapatkan respon positif dari siswa, pada uji coba tahap satu respon siswa menunjukan presentase 93%, sedangkan pada uji coba tahap kedua respon siswa menunjukan presentase 98,75%. Berdasarkan hasil validasi oleh ahli materi, media dan pedagogik serta hasil uji coba yang dilakukan media pembelajaran yang dikembangkan dinyatakan layak untuk digunakan Dengan demikian pengembangan media ular tangga tentang Lahirnya Pancasila dalam pembelajaran IPS untuk siswa kelas V Sekolah Dasar, layak digunakan siswa dalam proses pembelajaran.